Answer:
-6x is the slope
Step-by-step explanation:
1,-3
2,-9
-9+3 is -6
2-1 is 1
-6/1 is -6
<h3>Answer:</h3>
- f(1) = 2
- No. The remainder was not 0.
<h3>Explanation:</h3>
Synthetic division is quick and not difficult to learn. The number in the upper left box is the value of x you're evaluating the function for (1). The remaining numbers across the top are the coefficients of the polynomial in decreasing order by power (the way they are written in standard form). The number at lower left is the same as the number immediately above it—the leading coefficient of the polynomial.
Each number in the middle row is the product of the x-value (the number at upper left) and the number in the bottom row just to its left. The number in the bottom row is the sum of the two numbers above it.
So, the number below -4 is the product of x (1) and 1 (the leading coefficient). That 1 is added to -4 to give -3 on the bottom row. Then that is multiplied by 1 (x, at upper left) and written in the next column of the middle row. This proceeds until you run out of numbers.
The last number, at lower right, is the "remainder", also the value of f(x). Here, it is 2 (not 0) for x=1, so f(1) = 2.
Answer:
x = 2
Step-by-step explanation:
Multiply both sides by (x-5) and expand:
(x+4)/(x-5)*(x-5) = -2(x-5)
x+4 = -2x+10
Subtract 4 from both sides:
x+4-4 = -2x+10-4
x = -2x+6
Add 2x to both sides:
x+2x = -2x+6+2x
3x = 6
Divide both sides by 3:
3x/3 = 6/3
x = 2
The population standard deviation, σ = 1.68, the sample standard deviation, s = 1.95, the sample mean =7.23, and the sample size, n = 39.The test statistics is given by
T=(n - 1) (s / σ)²
= (39 - 1) (1.95 / 1.68)²
= 38 (1.35)= 51.196
Answer:
x=9
Step-by-step explanation:
First, distribute the 2 and each value in the parentheses.
2*x+2*5. This is the first half of the equation.
2*x+2*5= 3x+1 You can then simplify
2x+10=3x+1 Subtract 3x from both sides
(2x-3x)+10=(3x-3x[cancels out])+1
-x+10=1 Now subtract 10 from both sides
-x(10-10[cancels out to 0])=(1-10)
-x=-9 Since x is negative we need to solve for positive
x=9